The Tradition of Pacu on the Canoe as a Traditional Sports Culture for the People in Kuantan Singingi Regency, Riau Province (Journal of Physical Education and Sports, 2022)
Pacu Jalur Sampan is a traditional sporting event for the people of Kuantan Singingi Regency who use boats as a sporting venue. It is held on the banks of the Batang Kuantan River. The purpose of this study is to analyze the tradition, coaching method, management, development, and involvement of local government in Kuantan Singingi Regency's spur of the pacu jalur as a traditional sports culture. This study is descriptive qualitative in nature. Data collection procedures was using interviews, documentation, observation. Method of qualitative data analysis with a linear and hierarchical approach. According to the findings, the tradition of pacu jalur was originally used by peasants along the Kuantan river to transport crops and people. Then a race occurs on the racetrack. Determination, manufacture, and naming commence with the search for and felling of wood, which is preceded by a ceremony lead by a shaman. A shaman is in charge of the pre-race ritual. Where physical prowess and shaman control the path, the combination of magic and sport is quite near. The role of the government in the track is to promote the tourism industry. The conclusion is that the pacu jalur custom is a traditional sports culture that was formerly employed for daily transportation. Guidance and administration commence with the rite of locating and chopping wood, during which a jalur shaman had the duty to give jalur a name. The evolution of the pacu jalur sampan tradition through the performance of specific rituals throughout the race, combining magic and sports. The government's role are advertising and other forms of promotion.